2021
DOI: 10.53092/duiibfd.894094
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Volatility Interaction Between Vix Fear Index and Bist Sector Indices via CCC-Garch: Period of 2013-2020

Abstract: Küreselleşen finans piyasalarında yatırımcılar karar alırken ulusal bileşenler yanında uluslararası göstergeleri de dikkate almaktadır. Korku endeksi olarak da ifade edilen Volatilite Endeksi (VIX) Şikago Opsiyon Borsası tarafından hesaplanmakta ve hem politika yapıcılar hem de piyasa katılımcıları tarafından yaygın bir biçimde takip edilmektedir.Bu çalışmada da, Borsa İstanbul'dan seçilmiş 7 sektör endeksi ile VIX korku endeksi arasındaki volatilite etkileşimini ortaya koyabilmek amaçlanmaktadır. Çalışmada 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…It was determined that there was a cointegration relationship between the variables. It is seen that these results are similar to the studies in the literature Tuncay (2021), Kuzu (2019), Öner, İçellioğlu andÖner (2018), Başarır (2018) and Ruan (2018). There is no causal relation among the VIX index and gold futures.…”
Section: Conclusion and Policy Implicationssupporting
confidence: 89%
See 1 more Smart Citation
“…It was determined that there was a cointegration relationship between the variables. It is seen that these results are similar to the studies in the literature Tuncay (2021), Kuzu (2019), Öner, İçellioğlu andÖner (2018), Başarır (2018) and Ruan (2018). There is no causal relation among the VIX index and gold futures.…”
Section: Conclusion and Policy Implicationssupporting
confidence: 89%
“…However, he found that there is not any causal relation between the VIX index and the Brazilian stock market. Tuncay (2021) investigated the volatility spread among the sector indices with daily data for the period 2013 -2020 and VIX fear index. The multivariate CCC-GARCH model was used in the work.…”
Section: Introductionmentioning
confidence: 99%